Potential prevention and treatment of neurodegenerative disorders by olive polyphenols and hidrox. (April 2022) - Ontario, Maria Laura; Siracusa, Rosalba; Modafferi, Sergio; Scuto, Maria; Sciuto, Sebastiano; Greco, Valentina; Bertuccio, Maria Paola; Trovato Salinaro, Angela; Crea, Roberto; Calabrese, Edward J.; Di Paola, Rosanna; Calabrese, Vittorio
Abstract: Most chronic illnesses are caused by the biological reaction to an injury, rather than the initial injury or the injurious agent itselves as in neurodegeneration. With respect to this, notable attention is emerging on the therapeutic effects of dietary polyphenols for human health, able to counteract and neutralize oxidative stress and inflammatory processes involved in the etiopathogenesis of major neurodegenerative disorders, including Alzheimer's disease and Parkinson's disease. The acquired concept that cellular stress at low doses induces neuroprotective responses against degenerative processes is a frontier area of the neurobiological research focusing on the development of novel preventive and therapeutic interventions for neurodegenerative disorders. Notably, basal levels of prooxidant species are essential to promote adaptive redox cellular responses including vitagenes, tightly correlated to cell survival against age-related diseases. In this paper we discuss the concept of cellular stress response and hormesis and its applications to the field of neuroprotection and the potential therapeutic support provided by olive polyphenols, in particular hydroxytyrosol (HT)-rich aqueous olive pulp extract (Hidrox), as a pivotal activator of Nrf2 pathway and related vitagenes, and inhibitor of Keap1-Nrf2 interaction.Olive polyphenols are considered potential pharmacological modulators of neuroinflammation by upregulation of the Keap1/Nfr2/ARE pathway thus providing a strong rationale for treating neurodegenerative disorders Highlights: Hidrox is capable of reversing ROS production and inflammation via Nrf2 activation and transcription of vitagenes. Dietary polyphenols are promising neuroprotective oxidative stress modulators. Hormetic nutrition with Hidrox represents an excellent approach to develop novel personalized therapies.